Part a)
Answer:
As the L.H.S = R.H.S, so
is the solution to the equation
![3x + 4 = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/ykmmwmzmsf4638hh3ycj5molds1ja6p4vj.png)
Explanation:
Given the equation
![3x + 4 = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/ykmmwmzmsf4638hh3ycj5molds1ja6p4vj.png)
solving the equation for x = 1
substituting the value of x = 1 in the equation
![3\left(1\right)+\:4\:=\:7](https://img.qammunity.org/2021/formulas/mathematics/high-school/46cr6bmphdo9s2t49n5odtp9ct4uq6tybb.png)
![7=7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6lfctqntagsghe2vjtp9ilzohawzde97ix.png)
As the L.H.S = R.H.S, so
is the solution to the equation
![3x + 4 = 7](https://img.qammunity.org/2021/formulas/mathematics/high-school/ykmmwmzmsf4638hh3ycj5molds1ja6p4vj.png)
Part b)
Answer:
As the L.H.S = R.H.S, so
is the solution to the equation
Explanation:
Given the equation
![(x-3)/(2)=6](https://img.qammunity.org/2021/formulas/mathematics/high-school/gcriou34kus5yqdloy47dwhbkv9j541gnz.png)
solving the equation for x = 15
substituting the value of x = 15 in the equation
![(15-3)/(2)=6](https://img.qammunity.org/2021/formulas/mathematics/high-school/ktnuggx3wgwxiu5w4aiybcz4kj85i5lf02.png)
![(12)/(2)=6](https://img.qammunity.org/2021/formulas/mathematics/high-school/cmjzcgodm47tn9v1bn62qms03jejr4yjhl.png)
![6=6](https://img.qammunity.org/2021/formulas/mathematics/high-school/q5zte7vfaa6dnsedm3zs0wi6ghlk8i8xh1.png)
As the L.H.S = R.H.S, so
is the solution to the equation
Part c)
Answer:
As the L.H.S = R.H.S, so x = -3 in the equation is the solution to the equation
![x^2=-2x+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/qno9yhmtd1khkjn2ul06dvvydr77y0gl32.png)
Explanation:
Given the equation
![x^2=-2x+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/qno9yhmtd1khkjn2ul06dvvydr77y0gl32.png)
solving the equation for x = -3
substituting the value of x = -3 in the equation
![x^2=-2x+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/qno9yhmtd1khkjn2ul06dvvydr77y0gl32.png)
![\left(-3\right)^2=-2\left(-3\right)+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/py92gx1jjmfu1cathy2uvhw7qx3rrsooi8.png)
![9 = 6 + 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/tb6rf8p5sll7ee5d3hxfco9ndlo9y1ptp6.png)
![9 = 9](https://img.qammunity.org/2021/formulas/mathematics/college/f8jsubiijvgw5e7szkfy3bh028zd7nwzqq.png)
As the L.H.S = R.H.S, so x = -3 in the equation is the solution to the equation
![x^2=-2x+3](https://img.qammunity.org/2021/formulas/mathematics/high-school/qno9yhmtd1khkjn2ul06dvvydr77y0gl32.png)